In Silico Studies on Sennidines—Natural Dianthrones from Senna - Sebastian Szymanski; Irena Majerz (Biology, 2021)
The rapid development of technology allows for more accurate research of biological systems with the use of in silico methods. One of the tools is the quantum-chemical method used for determining the structure, properties and interactions of molecules of great pharmacological importance. The accuracy of theoretical models is increasing and can be a real help in biology, chemistry and pharmacy. The aim of the study is to determine the spatial structure and intramolecular interactions of sennidines—natural pharmaceutical substances present in Senna species. Calculations carried out in the gas-phase and in the solvent model, compared with the available experimental data indicate the possibility of sennidines to form conformers. QTAIM and NCI analysis suggests the presence of many intramolecular interactions in the sennidin structure. Taking into account the lowest energy optimized structure, it can be predicted that the sennidin in the gauche conformation will be present in the plant material. The single C-C bond connecting the anthrone moieties is elongated and its reduced Bond Dissociation Energy (BDE) could be the cause of an easy breakdown of the sennidin molecule into monoanthrones. This work contains data on theoretical, vibrational and electron excitation spectra, which can be used in the analysis of experimental samples.